Development of Interactive Multimedia for Human Reproduction System in Junior High School - Puspitasari, Dina Nafisa; Indriyanti, Dyah Rini; WH, Nugrahaningsih (FMIPA UNNES, 2019)
The study was aim to find out the effectiveness of the multimedia interactive for human reproduction system learning. The research was done at Junior High School 5 Pemalang with the design of research is Research and Development (R&D). The small scale trial of the product was done in 23 students with proportionate stratified random sampling method. The larger scale trial of the product was done in IX A class with Purposive Sampling Method and One Group Pre-test Post-test Experimental Design. The assessment from the experts to the multimedia interactive for system human reproduction learning obtains a high score as much as 89.58% for course assessment and 97.22% for media assessment. The results from the teacher and students response questionnaire in small scale trial obtain the average percentage as much as 100 % and 81.55 % respectively, which was high qualified. The effectiveness of Multimedia Interactive in learning could be seen in pretest and post test results with calculating N-gain and obtain N-gain 0.54, which was categorized as middle. Beside N-gain, the completeness of understanding the concepts become another effectiveness of multimedia interactive obtain 88% in classical completeness. The results of the study shows that the multimedia interactive was qualified and effective to enhance the students’ learning outcome in the course of system human reproduction.